Mechanical and thermal properties of triblock copolymer modified epoxy resins - Khatiwada, Shankar P; Thomas, Sabu; Saiter, Jean Marc; Lach, Ralf; Adhikari, Rameshwar (BIBECHANA, 2018)
We investigate the ways of improving thermal and mechanical properties of diglycidyl ether of bisphenol-A (DGEBA) based thermoset resin using diaminodiphenylsulphone (DDS) as hardener and using epoxidized polystyrene/polybutadiene-based triblock copolymers as modifier. The epoxidation was performed. The targeted chemical modification using meta-chloroperoxybenzoic acid (m-CPBA) of the copolymer was performed whereby the epoxidation of the butadiene chains mainly took place at 1,4 linkages. The modification copolymer was found to contribute in enhancing the mechanical performance of the blends with epoxy resin. The results indicated the formation of nanostructured morphology in the blends attributable to their enhanced impact strength. BIBECHANA 16 (2019) 196-203